Corrosion behavior of non-equilibrium Zr-Sn-Nb-Fe-Cu-O alloys in high-temperature 0.01 M LiOH aqueous solution and degradation of the surface oxide films. (15th May 2018) - Chen, Liang-Yu; Shen, Peng; Zhang, Lina; Lu, Sheng; Chai, Linjiang; Yang, Zhinan; Zhang, Lai-Chang
Highlights: Zr-Sn-Nb-Fe-Cu-O sample is finally annealed at a low-temperature and oversaturated. Second phase particles precipitate near the interface during long time corrosion. The second phase particles incorporate into oxide and degrade the property of oxide. The properties of oxide depend strongly on the substrate composition. The oxide with more defects and lower hardness is prone to delaminate. Abstract: This work uses qualitative analyses to investigate the corrosion behavior of two non-equilibrium Zr-Sn-Nb-Fe-Cu-O alloys in 0.01 M LiOH aqueous solution at 360 °C/18.6 MPa. Precipitates of second-phase particles (SPPs) and local recrystallization in the matrix are observed near the oxide/metal interface during extended periods of corrosion. Oxides formed on both alloys exhibit different hardness and gradually degrade. The oxides embedded with more SPPs show a lower hardness and therefore break down earlier. The variations of non-equilibrium microstructures of the substrates influence the properties of the oxides, thereby determining the corrosion performance of the alloys.